Evaluation Of Oil Palm Trunk Based Adhesive For Particleboard - Sulaiman, Nurul Syuhada (2013)
This study investigated the potential of starch extracted from oil palm trunk to be used as wood composite adhesive. Commercial rice starch was used as a comparison. The starch was modified with epichlorohydrin to impart it with better properties than its native form. The starch was then employed in the manufacturing of particleboard made from rubberwood particles. Particleboard manufactured using urea formaldehyde adhesive was used as a control particleboard samples. The physical and mechanical testing which includes moisture content, thickness swelling, water absorption, bending strength and internal bond strength of particleboard were evaluated based on the Japanese Industrial Standards. The particleboard was also characterized by using scanning electron microscopy, X-ray diffractometry analysis, thermogravimetric analysis, and differential scanning calorimetry analysis.